A sense of place : the political landscape in late medieval Japan - Spafford, David (Harvard East Asian monographs, 2013)
"Examines the vast Kantō region as a locus of cultural identity and an object of familial attachment during the political and military turmoil of the late fifteenth and early sixteenth centuries in Japan"--Provided by publisher